Fraud Prevention in Village Fund Managemant - Putri, Nur Alia; Mudrifah, Mudrifah; Irawan, Dwi; Wicaksono, Agung Prasetyo Nugroho (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
In the Village Fund Allocation (ADD), fraud can also occur because the provision of village funds every year increases so that it has the impact of fraud or fraud committed by irresponsible people who have been trusted by the community to manage village funds. The phenomenon of fraud cases or fraud in the village sector has often occurred every year. The purpose of this study is to test and analyze the relationship between Reporting Compliance, Internal Control System, Whistleblowing System, and Village Fund Management Fraud Prevention. This study uses quantitative research, Data Analysis Techniques in using SmartPLS 3.0, this technique is used to explain the relationship between exogenous variables and endogenous variables. The results of this study are financial reporting compliance has a positive effect on fraud prevention, the more compliance reporting is done effectively and well, fraud can be prevented, the internal control system and whistleblowing system negatively affect fraud prevention, this is because of the possibility of someone discomfort in reporting violations. Contribution in research to be the basis for assessment for village governments in fraud prevention.